Feto-Maternal Outcomes of Medical Induction of Labour in Post-Dated Pregnancies - Rimsha Sadia Bukhari, Ayesha Ashraf, Muhammad Javed, Mohammad Mohsin Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of feto-maternal outcomes of medical induction of labor in post-dated pregnancies. Patients and Methods: A total number 216 pregnant females with post-dated pregnancy were included in this study. Data regarding baseline study variables such as age, and BMI was collected for each patient. In all patients, medical induction of labor was done. Induction of labor was done using amniotomy, oxytocin or prostaglandins were given as per-local protocol. Feto-maternal outcomes in-terms of perineal lacerations, cesarean section, PPH, APGAR and NICU admission were measured. Results: Mean age of patients included in this study was 29.10±4.78 years. Mean body mass index (BMI) of patients was 25.82±5.04 kg/m2. Vaginal delivery was done in 142 (65.74%) and C-section was done in 74 (34.26%) patients. Perineal laceration was occurred in 118 (54.63%) patients, PPH in 06 (2.78%), APGAR score < 7 in 08 (3.70%) and 17 (7.87%) neonates were admitted it NICU. Conclusion: Medical induction of labor in post-dated pregnancies is a valuable option. It is associated with minimal feto-maternal complications in these patients.